Long-term prognostic significance of urinary sodium concentration in patients with acute heart failure. (1st March 2018) - Honda, Satoshi; Nagai, Toshiyuki; Nishimura, Kunihiro; Nakai, Michikazu; Honda, Yasuyuki; Nakano, Hiroki; Iwakami, Naotsugu; Sugano, Yasuo; Asaumi, Yasuhide; Aiba, Takeshi; Noguchi, Teruo; Kusano, Kengo; et al.
Abstract: Background: Lower urinary sodium concentration (UNa) may reflect impaired renal perfusion, higher neurohormonal activity and diuretic resistance. However, the prognostic impact of UNa in patients with acute heart failure (AHF) has not been fully elucidated. Methods: We investigate the association between UNa and clinical outcomes in 669 patients admitted with AHF in our prospective registry. Patients were stratified into tertiles based on UNa in a spot urine sample on admission. Results: Patients with lower UNa were more likely to have a history of prior heart failure admission, β-blockers and diuretics use, and had lower blood pressure and serum sodium level, and higher blood urea nitrogen, estimated glomerular filtration rate, blood glucose and troponin T levels on admission than those with higher UNa. Plasma renin activity, aldosterone, cortisol and dopamine levels were also significantly higher in patients with lower UNa (all p < 0.001). Furthermore, patients with lower UNa had significantly less weight loss, lower net fluid loss/furosemide equivalent dose and higher incidence of worsening renal function during hospitalization than those with higher UNa (all p < 0.01). During a median follow-up period of 560 days, lower UNa was significantly associated with the composite of all-cause death and worsening heart failure (p < 0.001). In multivariable Cox-proportional hazards model, UNa remained an independent determinant of long-term adverse events (HR, 1.24, 95% CI, 1.06–1.45, p = 0.006). Conclusions: Lower UNa was associated with worse long-term clinical outcomes along with increased neurohormonal activities, impaired response to diuretics and higher incidence of worsening renal function in patients with AHF.